The Famous Five: Five Fall Into Adventure - Enid Blyton (London, United Kingdom Hachette Children's Group, 2001)
Julian, Dick and Anne are really worried - George and her devoted Timmy have just disappeared! Not only that, somebody has broken into Kirrin Cottage. Could there be a connection? The Famous Five think so, but it's going to be tough getting to the bottom of this mystery when there's only three of them . . .
Keywords: Mystery -- Mystery